Pergaulan Bebas Menurut Perspektif Hukum Adat dan Hukum Islam - Sukri, Ahmad; Pratiwi, Delly; Fadilah, Riska; Syamsiah, Syamsiah; Alkaff, Fitriyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This journal discusses the phenomenon of free association in the context of customary law and Islamic law. Free association, which is characterized by free interaction without the constraints of social and religious norms, is increasingly prevalent in the modern era. This journal analyzes how customary law and Islamic law view free association, as well as the legal and social implications of this phenomenon. Through literature studies and comparative legal analysis, this journal identifies customary and Islamic legal norms that regulate association between men and women. On the one hand, customary law has a variety of norms that regulate social interaction, including free association, with significant variations between regions. On the other hand, Islamic law has clear principles regarding association between the opposite sex, emphasizing the importance of maintaining chastity and honor. This journal then discusses the legal and social implications of free association, including the potential for violations of norms, social conflict, and impacts on morality. This journal also highlights efforts that can be made to overcome free association, such as moral education, strengthening cultural values, and fair and effective law enforcement. This journal is expected to contribute to a more comprehensive understanding of free association in the context of customary law and Islamic law, as well as open up a space for discussion to find appropriate solutions in dealing with this phenomenon.